EFEKTIFITAS PENGEMBANGAN WONDERSHARE QUIS CREATOR DALAM MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN KRITIS SISWA SD - Jumiasih, Jumiasih; Sukartiningsih, Wahyu; Hendratno, Hendratno (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This technological development affects the Indonesian language learning model at all levels of education, especially in elementary schools (SD). In teaching and learning activities, one of which is an evaluation tool is needed. This study aims to determine the Effectiveness of Developing an Evaluation Tool Based on Wondershare Quis Creator to Measure Critical Reading Comprehension Skills in Grade 6 Elementary School Students. Research methods carried out include Research and Development (research development). The research subjects were 6th grade students of SDN Ngagel 1/394 Surabaya aged 8-11 years, totaling 50 students. The results of this study showed that the critical reading comprehension skills of grade 6 students were in the high category with an average n-gain score of 0.76. The conclusion of this study is that the effectiveness of the Wondeshare Quis Creator-based evaluation tool to improve the critical reading skills of 6th grade elementary school students has increased significantly.